Impact of dust addition on the metabolism of Mediterranean plankton communities and carbon export under present and future conditions of pH and temperature - Frédéric Gazeau; France Van Wambeke; Emilio Marañón; Maria Pérez-Lorenzo; Samir Alliouane; Christian Stolpe; Thierry Blasco; Nathalie Leblond; Birthe Zäncker; Anja Engel; Barbara Marie; Julie Dinasquet; et al. (PANGAEA, 2021)
Although atmospheric dust fluxes from arid as well as human-impacted areas represent a significant source of nutrients to surface waters of the Mediterranean Sea, studies focusing on the evolution of the metabolic balance of the plankton community following a dust deposition event are scarce, and none were conducted in the context of projected future levels of temperature and pH. Moreover, most of the experiments took place in coastal areas. In the framework of the PEACETIME project, three dust-addition perturbation experiments were conducted in 3000.167emL tanks filled with surface seawater collected in the Tyrrhenian Sea (TYR), Ionian Sea (ION) and Algerian basin (FAST) on board the R/V Pourquoi Pas? in late spring 2017. For each experiment, six tanks were used to follow the evolution of chemical and biological stocks, biological activity and particle export. The impacts of a dust deposition event simulated at their surface were followed under present environmental conditions and under a realistic climate change scenario for 2100 (ca. +30.167em°C and -0.30.167empH units). The tested waters were all typical of stratified oligotrophic conditions encountered in the open Mediterranean Sea at this period of the year, with low rates of primary production and a metabolic balance towards net heterotrophy. The release of nutrients after dust seeding had very contrasting impacts on the metabolism of the communities, depending on the station investigated. At TYR, the release of new nutrients was followed by a negative impact on both particulate and dissolved 14C-based production rates, while heterotrophic bacterial production strongly increased, driving the community to an even more heterotrophic state. At ION and FAST, the efficiency of organic matter export due to mineral/organic aggregation processes was lower than at TYR and likely related to a lower quantity/age of dissolved organic matter present at the time of the seeding and a smaller production of DOM following dust addition. This was also reflected by lower initial concentrations in transparent exopolymer particles (TEPs) and a lower increase in TEP concentrations following the dust addition, as compared to TYR. At ION and FAST, both the autotrophic and heterotrophic community benefited from dust addition, with a stronger relative increase in autotrophic processes observed at FAST. Our study showed that the potential positive impact of dust deposition on primary production depends on the initial composition and metabolic state of the investigated community. This impact is constrained by the quantity of nutrients added in order to sustain both the fast response of heterotrophic prokaryotes and the delayed one of primary producers. Finally, under future environmental conditions, heterotrophic metabolism was overall more impacted than primary production, with the consequence that all integrated net community production rates decreased with no detectable impact on carbon export, therefore reducing the capacity of surface waters to sequester anthropogenic CO2.